The Physical Oceanography Conditions of the Northern Waters of Bengkalis Island Riau Province - Wijayanto, Doddy; Ghalib, Musrifin; Nasution, Syafruddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in June 2017 in North Waters of Bengkalis Island, Riau Province. The Aim of research was to describe the condition of physical oceanography and to know the effect of the activity that occurs on the condition of the North water of Bengkalis Island. The research used survey method. Physical oceanography data obtained were presented in the form of chat the map and discussed descriptively. Based on the research it showed that value of water depth range from 2,75 – 52,87 m and average value of 28,70 m. The temperature of the waters ranges from 31,87 ºC – 27,31 ºC and average of 29,35 ºC. The velocity of currents was speed, category, the current velocity ranges from 0,30 to 0,73 m/s and the transparency waters is influenced by the substrate of coastal waters ie mud. Transparency range from 45,5 to 23,5 cm.Keywords: Oceanography, Aquatic Physics, Salinity, Temperature, North Bengkalis Island